Chayote, Sechium edule (Jacq.) Sw. - Lira-Saade, Rafael; Leibniz Institute of Plant Genetics and Crop Plant Research; International Plant Genetic Resources Institute (1996)
The variable fruits and roots of chayote is an important element in the diet in many parts of Latin America, and it is a valuable export crop. This monograph provides an overview of existing knowledge of the genus with emphasis on genetic resources. Chapters cover the following topics: taxonomy and nomenclature, botany, floral biology, evolution, wild relatives, uses, diversity, breeding, production, ecology, agronomy, pests and diseases, and limitations of the crop, research needs and prospects. An appendix details research contacts and centres of research. (Abstract © CAB ABSTRACTS, CAB International)